BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP KAPITALISASI PASAR SAHAM - Nasution, Lokot Zein (Publikasi Penelitian Terapan dan Kebijakan, 2013)
The main objective of this study was to measure the effect of capital market and the exchange rate of the composite stock price index. This study uses secondary data and using multiple linear regression analysis where there is a classical hypothesis testing and the assumptions therein. The empirical results show that the capital market has positive influence on the movement of the stock price index and while the rupiah against the dollar negatively influential to the movement of the stock price index.